The practice and implementation of zakat gold in Selangor / Hazirah Salleh - Salleh, Hazirah (Academy of Contemporary Islamic Studies, 2018)
Gold is a precious and useful metal. History has proved throughout the early Islamic civilization, gold is the main medium for silver exchange (barter) and transactional tools for obtaining the necessary products. The obligation of zakat gold has been set by the fatwa of the states and it is not the same between one state and another state. Many Muslims in Malaysia have the perception that jewellery is not subjected to zakat as much as it is available provided it is used as a women's jewellery. Many do not know about zakat obligations in the practice of the states. This study examines the real concept of zakat gold. This study also aims to identify the practice and implementation of gold zakat in Selangor which is required on zakat gold. The main method used in this study was the interview method, of which 3 were selected to be interviewed is officer of Lembaga Zakat Selangor, an expert academic of zakat gold and also zakat payers. The preliminary findings of this study are expected to help Lembaga Zakat Selangor in raising the awareness of the Selangor community on the obligation of this zakat gold. The study also contains several approaches and recommendations to ensure zakat institutions can be strengthened and zakat collection funds can be increased.